SISTEM KONVERSI HAK ATAS TANAH ADAT KAMPUNG NAGA - Didik Wihardi; Andri Hernandi; Rizki Abdulharis; Alfita Puspa Handayani (Fakultas Seni Rupa dan Desain ITB, 2010)
Customary land is land controlled by a certain indigenous communities in an area spread across Indonesia. PMNA No.5 in the year 1999 stated that the lands are parcels of land on which customary rights are of a particular customary law. However, the term customary land has not accommodated in the law. The existence of customary land often causes problems between individuals, people with groups, even groups of people with other community groups. In some areas in West Java such as Kampung Naga, there are still people who still stick to the customary law as a regulatory or legal source they must obey. However, the impact of the use of customary law for the regulation of rights on land they own. It is supported by evidence of qualitative ownership, because these lands have not been registered. The root cause of the above is still a dualism between the national land law and customary law, leading to uncertainty, a situation contrary to the philosophy and purpose of the law. The second root causes of the conversion system of land rights of indigenous land rights to one of land rights in the BAL is still completely governed by the laws of the implementation process of conversion. Referring to the two problems above, it is necessary to change the rules governing the land rights of indigenous land rights to the new land rights by BAL. Rules are explained through a process of conversion of customary land rights that should be regulated in detail by the laws and government regulations. The purpose of writing this article is to identify the conversion process rights to customary land rights which is listed on the BAL based on the provisions of BAL and conversion of PP 24 in 1997.